Distinct Bottom-Water Bacterial Communities at Methane Seeps With Various Seepage Intensities in Haima, South China Sea - Li, Xiaopeng; Dai, Zehan; Di, Pengfei; Feng, Junxi; Tao, Jun; Chen, Duofu; Li, Niu; Li, Yazi (Frontiers in Marine Science, 2021)
Methane seeps are chemosynthetic ecosystems in the deep-sea environment. Microbial community structures have been extensively studied in the seepage-affected sediments and investigation in the water column above the seeping sites is still lacking. In this study, prokaryotic communities in the bottom water about 50 cm from the seabed at methane seeps with various seepage intensities in Haima, South China Sea were comparatively studied by using 16S ribosomal RNA gene sequencing. These sites were assigned based on their distinct methane content levels and seafloor landscapes as the non-seepage (NS) site, low-intensity seepage (LIS) site, and high-intensity seepage (HIS) site. The abundances of the dominant phyla Proteobacteria, Bacteroidetes, and Actinobacteria differed significantly between NS and the two seepage sites (p < 0.05). Alpha diversity differed among the three sites with the HIS site showing the lowest community diversity. Principal component analysis revealed highly divergent bacterial community structures at three sites. Many environmental variables including temperature, alkalinity, pH, methane, dissolved organic carbon (DOC), and inorganic nutrients were measured. Redundancy analysis indicated that methane content is the key environmental factor driving bacterial community variation (p = 0.001). Linear discriminant analysis effect size analysis identified various differentially enriched genera at the LIS and HIS sites. Phylogenetic analysis revealed close phylogenetic relationship among the operational taxonomic units of these genera with known oil-degrading species, indicating oil seepage may occur at the Haima cold seeps. Co-occurrence networks indicated that the strength of microbial interactions was weakest at the HIS site. This study represents a comprehensive comparison of microbial profiles in the water column of cold seeps in the SCS, revealing that the seepage intensity has a strong impact on bacterial community dynamics.